The relationship between heart rate and mortality of patients with acute coronary syndromes in the coronary intervention era: Meta-analysis. Issue 46 (November 2016) - Xu, Tan; Zhan, Youqin; Xiong, Jianping; Lu, Nan; He, Zhuoqiao; Su, Xi; Tan, Xuerui
Abstract: Background: Most of acute coronary syndromes (ACS) were receiving intervention treatment a high overall rate of coronary angiography in the modern medical practice. Consequently, we conduct a review to determine the heart rate (HR) on the prognosis of ACS in the coronary intervention era. Methods: PubMed, EMBASE, MEDLINE, and the Cochrane Library was systematically searched up to May 2016 using the search terms "heart rate, " "acute coronary syndrome, " "acute myocardial infarction, " "ST elevation myocardial infarction, " "non-ST-segment elevation." The outcome of interest was all-cause mortality. All analyses were performed using Review Manager. Results: Database searches retrieved 2324 citations. Eleven studies enrolling 156, 374 patients were included. In-hospital mortality was significantly higher in the elevated HR group compared to the lower HR group (pooled RR 2.04, 95%CI 1.80–2.30, P  < 0.0001). Individuals with elevated admission HR had increased risk of long-term mortality (Pooled RR = 1.63, 95%CI 1.27–2.10, P  = 0.008) compared to lower admission HR. The pooled results showed elevated discharge and resting HR were related to increased mortality of patients with ACS (pooled RR 1.88, 95% CI 1.02–3.47, P  = 0.04; pooled RR 2.14, 95%CI 1.37–3.33, P  < 0.0001, respectively). Conclusion: Elevated HR may increase the mortality of ACS patients in the percutaneous coronary intervention era.